MAQĀṢIDAL-SYARĪ’AH DALAM KAJIAN TEORI EKONOMI ABU ISḤĀQ Al-SYĀṬIBĪ - fasya, fasya (Al - Muamalat, 2017)
Al-SyÄá¹ibi offered a concept its called maqÄá¹£id ash-shari'a. The purpose of this concept is protecting human rights maslahat. It can be realize if five prime unsures of live protected and implementated, they are religion, soul, rasionality, chilhood and property. MaqÄá¹£id ash-shari'a contains of three grades, they are á¸arÅ«riat, á¸¥ajiyat and taá¸¥siniyat. á¸¤ajiyat completed á¸arÅ«riat, taá¸¥siniyat completedá¸¥ajiyat grade thoght á¸arÅ«riat is the base of á¸¥ajiyat and taá¸¥siniyat. So far, he explained thats all activity or all secundary orientations must be ignore even there are high purpose in the world (á¸arÅ«riyat and á¸¥ajiyat).